A simulation study on the effect of CO2 injection on the performance of the GTL process. (8th May 2020) - Al-Yaeeshi, Ali Attiq; AlNouss, Ahmed; McKay, Gordon; Al-Ansari, Tareq
Highlights: A techno-economic-environmental performance for CO2 utilisation within the GTL process is conducted. Various reforming technologies have been analysed. The GTL process is simulated using Aspen HYSYS software package. The optimum operating conditions of steam to carbon ratio and CO2 flow rate are verified. The production enhancement, CAPEX and OPEX, and the direct/indirect CO2 emissions is determined. Abstract: This study enhances the efficiency of the Fischer-Tropsch process through CO2 injection. Syngas production in the reforming units is simulated for three cases; two cases for auto-thermal reforming (ATR) with varying steam flow rates and a case for steam-methane reforming (SMR). Outcomes demonstrate an enhancement in the total refined production and the optimisation of the growth probability (α) in the Anderson–Schulz–Flory (ASF) relationship and H2 :CO proportion. Aspen HYSYS simulation outputs indicate that the ATR reformer at a steam flow rate 3223 T/D and a CO2 flow rate 1500 T/D represents an optimal scenario for product enhancement. Furthermore, a techno-economic analysis indicates that the ATR (C3) option is the best performing economically with a net profit per input of natural gas and refined product output generating 542.94 ($/T) and 722.74 ($/T) respectively. The environmental analysis demonstrates lowest carbon emissions with 1.76 and 2.34 kg CO2 -e/T.